(untitled) (ModaPalavra e-periódico, 2020)
Workwear is worn to standardize wearers throughout the workday, and their textile materials come in direct contact with the skin. However, this type of clothing is often purchased in large quantities and are made of economically viable textile materials for employers. When comfort is not a priority, the user may be adversely af fected by prolonged use of parts. This article investigates the user’s perception of tactile comfort, which is the touch of the fabric on the skin, and the thermal perception or sensation of heat or cold caused by the textile sample. The field trial was co nducted with 20 participants using five textile samples commonly used on shirts, T - shirts, and trousers for general service workwear and one for sportswear. Samples were tested in pairs between flat and knitted fabrics. The results indicate the participant s’ preference for sportswear because it is softer and fresher to the skin.